2009
DOI: 10.1136/oem.2008.044180
|View full text |Cite
|
Sign up to set email alerts
|

Residential exposure to radiofrequency fields from mobile phone base stations, and broadcast transmitters: a population-based survey with personal meter

Abstract: Objectives: Both the public perceptions, and most published epidemiologic studies, rely on the assumption that the distance of a particular residence from a base station or a broadcast transmitter is an appropriate surrogate for exposure to radiofrequency fields, although complex propagation characteristics affect the beams from antennas. The main goal of this study was to characterise the distribution of residential exposure from antennas using personal exposure meters. Methods: A total of 200 randomly select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
51
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 21 publications
0
51
0
1
Order By: Relevance
“…In fact, objectively measured distance to an MPBS is only weakly correlated with actual exposure from that MPBS. 46,47 Interestingly, our review found the strongest symptomatic effects in two studies using measured distance, 1,27 which makes these findings arguable as well.…”
Section: Discussionmentioning
confidence: 79%
“…In fact, objectively measured distance to an MPBS is only weakly correlated with actual exposure from that MPBS. 46,47 Interestingly, our review found the strongest symptomatic effects in two studies using measured distance, 1,27 which makes these findings arguable as well.…”
Section: Discussionmentioning
confidence: 79%
“…The EME Spy 100 (Satimo, France) PEM, used as a measurement tool in this study, is capable of receiving the FM radio frequency band in Korea [19]. In Europe, EME Spy 120 (Satimo, France) products from the same company have been used for other research [16,17,34,35]. Personal exposure meter measurements made for 24 h involve all exposure frequencies encountered in a daily life as well as whole-body exposure.…”
Section: Discussionmentioning
confidence: 99%
“…They have been employed in epidemiological research in recent years [Kühnlein et al, 2009;Viel et al, 2009;Frei et al, 2009a]. Nevertheless, some constraints have been reported in the scientific community, such as the shadowing effect caused by the subject's body [Blas et al, 2007], false summation of signals within the same band, out-of-band responses, and high calibration factors in a few frequency bands [Neubauer et al, 2010].…”
Section: Introductionmentioning
confidence: 97%